Merjeni in izračunani fotobiološki učinki odbite svetlobe na ljudi - Malovrh Rebec, Katja (Gradbeni vestnik, 2018)
When designing light, the calculations only partially predict the effects of light on the users. In addition to the well-known image forming effects based on rod and cone responses, the light elicits non visual effects as well. The latter is not related to the orientation in ambient, but communicates key information related to hormones secretion. The peak of this perception is in the blue part of the spectrum of visible light. Unfortunately, the responses of these photoreceptors cannot be predicted with parameters currently used in the lighting design practice, so the effects on users are often ignored. An additional challenge is the established practice where the light effects are communicated in lux, which means that they are multiplied by the average human daily vision. Such an approach is not suitable for the evaluation of non-visual effects, because they have a different action curve. We have measured the spectral composition of the reflected daylight in the model room, because we were interested in the differences in image and non-visual forming effects of differently painted walls. Blue and violet walls stimulate observers' non-image forming perception more than image forming in both gazing directions. In both gazing directions orange walls stimulate non-image forming effects far less than the image forming ones. Green walls revealed bigger non image forming effects then non-image forming effects in the forward look, and the other way around in the gaze directed on the table.
Keywords: daylight; dnevna svetloba; fotobiološki učinki; melatonin; odbita svetloba; photobiological effects; reflected light; spectral composition of light; spektralna sestava svetlobe